Structural analysis of layered evaporites using internal deformation patterns: Examples from Santos and Campos basins, Brazil. (August 2022) - Bose, Shamik; Sullivan, Michael
Abstract: The Santos and Campos basins, offshore southeastern Brazil, contain layered evaporite sequences (LES) deposited during the Late Aptian, marking the end of lacustrine and beginning of restricted marine conditions. Density and velocity differences between evaporite minerals such as halite, anhydrite, carnalite, tachyhydrite and other bittern salts result in strong seismic impedance contrasts and therefore enable excellent stratal imaging of internal salt deformation. Different acoustic responses allow a detailed analysis of the internal deformation of evaporites, with the corresponding mechanical properties providing constraints on regional salt flow in the Santos and Campos basins. Detailed mapping and analysis of deformed LES support conclusions from cross-section restorations and provide insight on local salt flow and deformation mechanisms. This study utilizes kinematically restored regional sections to characterize overall basin-wide salt flow, while leveraging salt facies and their control on internal salt fold styles to demonstrate localized salt deformation. The important results from this study are the following. a) Santos and Campos basins are linked extension-contraction systems, however pre-existing basin-wide changes in paleo-topography represents a fundamental control in the overall salt flow, accounting for much of the downdip contraction in the middle of the basins rather than the toe of the system. b) Salt mobilization due to gravity initiated early and there is evidence that it was contemporaneous with evaporite deposition in many parts of the basins. Intrasalt unconformities and stratigraphic features are presented to support this conclusion. c) Mechanical stratigraphy within the LES play an important role in controlling intra-salt structural styles, and their fold interference patterns can be used to understand salt deformation in great detail. These results can be applied to better investigate a spectrum of salt tectonic problems in the basins and elsewhere, such as regional and localized salt flow, sub-regional prediction of weld kinematics and local prediction of weak salt units for drilling hazard analysis.